Paralympic pathways - Legg, V.; Orr, K.; Patatas, J. M.; Pankowaik, A.; Wong, J.; Higgs, C.; Hamamoto, G. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
The performances being witnessed at the recent Paralympic Games have resulted in part from varying development systems. To help us understand how these systems and pathways have been created and how they can be changed and improved in the future, a variety of challenges and opportunities are presented in this chapter. We also reflect on two specific pathway systems including those in Canada and Sub-Saharan Africa. Finally, the remaining gaps and anticipated shifts in Paralympic athlete pathways are discussed with the hopes of providing a roadmap for improved future opportunities in sport for persons with disability.